2019
DOI: 10.1101/2019.12.23.880021
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Exaptation of two ancient immune proteins into a new dimeric pore-forming toxin in snails

Abstract: The Membrane Attack Complex-Perforin (MACPF) family is ubiquitously found in all kingdoms. They have diverse cellular roles but MACPF but pore-forming toxic function are very rare in animals. Here we present the structure of PmPV2, a MACPF toxin from the poisonous apple snail eggs, that can affect the digestive and nervous systems of potential predators. We report the three-dimensional structure of PmPV2, at 15 Å resolution determined by negative stain electron microscopy (NS-EM) and its solution structure by … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Comparative genomic analysis together with expression patterns and proteomic validation showed that although these lectin and MACPF are present in the genomes of four species of the family, as well as in the genomes of other Mollusks, only in Pomacea these two proteins experienced extensive gene expansion by tandem duplication and neofunctionalization into the PV2 complex, which is expressed as such only in an accessory gland of females and transferred to eggs (30). Although the immune role of these two proteins are largely unexplored in snails, a PV2-67-like protein found in the kidney of the snail Littorina littorea showed overexpression when infected with a trematode parasite (31), indicating a putative immune function in the common ancestor of mollusks MACPF (12). In addition to their immune role, another prominent role of animal MACPFs is in the embryonic development of several organisms, ranging from sea urchins to mammals (32).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparative genomic analysis together with expression patterns and proteomic validation showed that although these lectin and MACPF are present in the genomes of four species of the family, as well as in the genomes of other Mollusks, only in Pomacea these two proteins experienced extensive gene expansion by tandem duplication and neofunctionalization into the PV2 complex, which is expressed as such only in an accessory gland of females and transferred to eggs (30). Although the immune role of these two proteins are largely unexplored in snails, a PV2-67-like protein found in the kidney of the snail Littorina littorea showed overexpression when infected with a trematode parasite (31), indicating a putative immune function in the common ancestor of mollusks MACPF (12). In addition to their immune role, another prominent role of animal MACPFs is in the embryonic development of several organisms, ranging from sea urchins to mammals (32).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to those proteins PmPV2 is maternally transferred to the eggs, where it is massively accumulated during the early developing stages, before the embryo consumes it (33). However, PV2 structure lacks some key structural features described in developmental MACPFs, such as absence of ancillary domains and shorter TMH1 (12,32). Finally, a less-extended group of animal MACPFs also act as toxins such as those from some cnidarians and the stone fish, where they play a role in prey capture (22,34).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PRF appears to only form ordered ring-like structures upon transition to the final pore form ( 94 ). Deviations of the common mechanism also are evident in pleurotolysin and perivitellin-2, which are two-component toxins ( 12 , 13 ).…”
Section: Mpeg1 Structure and Mechanismmentioning
confidence: 99%
“…; SPECT, MAOP) ( 7 , 8 ), as venom components ( e.g. sea anemone toxin PsTX-60B, stonustoxin, perivitellin-2) ( 9 12 ), and nutrition ( e.g. fungi; pleurotolysin) ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%